Design development process and user involvement in healthcare projects - Mohd Nawawi, Norwina (2019)
Introduction to the Design Process Development till commissioning in Hospital Projects to Non-Architect/Non-technical stakeholders of the project team-medical personnel as USERS. The presentation informed the role of users in the process and the significance of their involvement for the success of the project to be fit for purpose